Pharmacogenomics and genetic ancestry in Colombia: a study on all variant drug annotations of PharmGKB - Acosta-Monterrosa, Andy A.; Montoya-Quintero, Kevin Fernando; Galván-Barrios, Johana; Rojas Torres, Indiana Luz (Frontiers in Pharmacology, 2025)
BackgroundTo generate an ancestry-resolved pharmacogenomic (PGx) landscape for Colombia by integrating all PharmGKB variant-drug annotations with local allele-frequency data, thereby quantifying inter-ancestry differences of clinical relevance and exposing evidence gaps that hinder equitable precision medicine.MethodsWe conducted a cross-sectional analysis of 4,462 PharmGKB variant annotations (1994–2024), retaining 1,216 significant single-nucleotide polymorphisms (SNPs) reported in 552 studies. Allele frequencies were extracted for five Colombian populations: two predominantly African (Palenque [PLQ], Chocó [CHG]) and three predominantly European (ATQCES, ATQPGC, CLM), from the CÓDIGO database. Spearman correlations compared population-specific PGx profiles; SNPs with >25 percentage-point frequency differentials were tabulated.ResultsEuropean ancestry dominated the global evidence base, representing 51.5% of 651,532 participants, while African ancestry accounted for only 0.46% (n = 3,031). Strong correlations were observed among European-leaning Antioquians (r2 ≥ 0.90), whereas PLQ exhibited inverse or negligible correlations with those groups (r2 = −0.20 to −0.02) and minimal similarity with CHG (r2 = 0.12). Twenty-eight SNPs were frequent in PLQ (>75%) but rare in Europeans (<50%), and 44 showed the opposite pattern. Notable examples include CYP3A4 rs3735451-C (rivaroxaban; 87.1% vs. 23.2%), CYP3A5 rs776746-T (tacrolimus; 85% vs. 23.5%), and rs55881666-C (duloxetine; 15% vs. 84%). Globally, 71.5% of PGx studies originated in high-income countries.ConclusionLarge, clinically actionable allele-frequency contrasts and pronounced discovery biases confirm the need for ancestry-aware PGx testing and locally calibrated dosing algorithms in Colombia. The analytic framework and variant catalogue generated knowledge to operationalize precision pharmacotherapy across admixed Latin-American populations.